Association of Serum Ferritin and Iron with C-reactive protein in Menopausal Women with Cardiovascular Disease in Erbil-City - Omar Ahmad, Nihayat; Hatem Mohammed, Halala (Tikrit Journal of Pure Science, 2025)
Cardiovascular diseases (CVD) are recognized as the number one cause of morbidity and mortality globally. The purpose of this research is to evaluate the impact of iron and ferritin levels in serum menopausal women and to determine the correlation between CRP with iron and ferritin in menopausal women that have CVD. This case-control study was carried out on (180) participants (40-69 years) of age with and without CVD. The following parameters were measured (iron, ferritin, and C-reactive protein). Menopausal women with CVD had significantly higher mean serum levels of iron (67.13±2.178 mg/dL vs 59.36±2.131 mg/dL) (p=0.0117) along with serum ferritin level (114.0±5.760 ng/mL vs 73.29±5.001 ng/mL) (p<0.0001) and CRP level (1.305±0.1584 mg/dL vs 0.4412±0.05976 mg/dL) (p<0.0001) in comparison with healthy menopausal women, and the results of this study shows a significant and positive correlation between Ferritin with CRP in menopausal women with CVD (r=0.37, p=0.0003). In conclusion, the serum level of ferritin, iron, and CRP higher significantly in menopausal patients compared with healthy menopausal women.